Global and regional ionospheric response to a moderate storm in South America and Antarctica using a multi‐instrumental approach - Melendi, Y. D. (2025)
In this study, we investigate the ionospheric disturbances caused by a moderate geomagneticstorm (maximum Kp = 6) occurring between 26th February and 1 March 2023. Ionospheric response for thecoupling between the solar wind, magnetosphere, and ionosphere systems can be observed across variousregions of the globe and it may vary according to the local/regional background ionospheric conditions. Weanalyzed space and ground‐based instruments (e.g., ionosondes, total electron content, GUVI imager,incoherent scatter radar) covering from Antarctica to equatorial latitudes in South America. From a globalperspective, we observed two ionospheric storms. The first, with a negative phase observed as a significantdecrease (>30%) in the F2‐layer critical frequency (foF2), occurred on February 27th at 01:00 UT. This negativephase storm was observed in all the considered regions, with the intensity progressively decreasing from higherto lower latitudes. It is worth mentioning that, for the Antarctic station, we consider the local regime of theWeddell Sea Anomaly. The second ionospheric storm occurred during the recovery phase of the geomagneticstorm on 28th February. In this last case, an enhancement above 30% in foF2 was observed only in the low‐latitude station. Subsequently, the geomagnetic storm produced a super fountain effect at the EquatorialIonization Anomaly resulting in the enhancement of foF2.